Method for assisting in generating perovskite in-situ film through interface protonation reaction

By spin-coating the perovskite precursor solution on the acidic substrate and assisting crystallization with protonation reaction, the problems of rapid crystallization and high defect density of tin-based perovskite films are solved, and film formation of high-quality films and the preparation of high-performance PeLED devices are achieved.

CN119604162APending Publication Date: 2025-03-11WENZHOU XINXIN TAIJING TECH CO LTD +1

Patent Information

Application Number
CN202411574923.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

During the crystallization process, tin-based perovskite films have problems such as rapid crystallization, low coverage, rough morphology and high defect density, which affect their luminous performance.

Method used

By spin-coating the perovskite precursor solution on the acidic substrate, the complex mesophase is formed, and the conversion of the mesophase to the perovskite film is induced during the annealing process, while the addition of thiocyanate is added to inhibit Sn2+ oxidation.

Benefits of technology

It effectively improves the film coverage and morphological quality, reduces defect density, and improves the luminous performance of tin-based PeLED devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119604162A_ABST
    Figure CN119604162A_ABST
Patent Text Reader

Abstract

The invention relates to a method for generating a perovskite in-situ film through assistance of an interface protonation reaction, and the method comprises the following steps: S1, spin coating: carrying out the spin coating of a perovskite precursor solution on an acidic substrate, and forming a complex intermediate phase; the perovskite precursor solution comprises a tin halide, a monovalent cation halide, thiocyanate and an ethylenediamine derivative; s2, annealing: heating and annealing the intermediate phase of the complex on a heating stage, and inducing conversion of the intermediate phase of the complex to the tin-based perovskite thin film through a protonation reaction between the acidic substrate and the ethylenediamine derivative; the chemical structure of the tin-based perovskite is ASnX3. According to the method, the protonation reaction of the acidic substrate and the perovskite interface is utilized to assist in generating high-quality perovskite, the morphology of the thin film is effectively improved, and a high-brightness PeLED device is further prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of perovskite quantum dot film preparation, and in particular relates to a method for in-situ film formation of perovskite assisted by interface protonation reaction. Background Art

[0002] Metal halide perovskites include lead-based perovskites, tin-based perovskites, and copper-based perovskites. They are crystalline semiconductor materials that can be processed through low-temperature solution processes. They have the advantages of adjustable band gap, narrow half-width of luminescence, high fluorescence quantum yield, high defect tolerance, simple preparation, and low cost. They are very suitable for use in light-emitting diodes (LEDs) based on solution processing. At present, high-performance perovskite light-emitting diodes (PeLEDs) mainly rely on lead-based perovskites, and lead poses a great threat to the environment and human health. Therefore, lead-free perovskites have become one of the important research directions in the field of perovskites.

[0003] Since tin has an electronic structure and ionic radius similar to that of lead, tin-based perovskites have become a powerful substitute for lead-based perovskites. However, as is generally known to those skilled in the art, the crystallization speed is ranked from fast to slow as follows: tin-based perovskites > lead-based perovskites > copper-based perovskites. 2+ Easy oxidation problem. Rapid crystallization will lead to low film coverage and rough morphology, and easily introduce a large number of defects in the perovskite, seriously affecting the luminescence performance of Sn-based PeLED. 2+ Oxidation will lead to an increase in tin vacancy defects in the film, which will in turn reduce the luminescence efficiency of the perovskite.

[0004] Therefore, when researchers develop tin-based perovskites to replace lead-based perovskites, they must solve the above technical problems, so there is room for improvement. Summary of the invention

[0005] The purpose of the present invention is to provide a method for in-situ film formation of perovskite assisted by interfacial protonation reaction. The present invention assists in the generation of high-quality perovskite by utilizing the protonation reaction between the acidic substrate and the perovskite interface, effectively improves the film morphology, and further prepares a high-brightness PeLED device.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A method for in-situ film formation of perovskite assisted by interface protonation reaction comprises the following steps:

[0008] S1, spin coating: spin coating a perovskite precursor solution on an acidic substrate to form a complex intermediate phase; the perovskite precursor solution includes a tin halide, a monovalent cation halide, a thiocyanate, and an ethylenediamine derivative;

[0009] S2, annealing: heating and annealing the complex intermediate phase on a hot stage, inducing the transformation of the complex intermediate phase into a tin-based perovskite film through a protonation reaction between the acidic substrate and the ethylenediamine derivative; the chemical structure of the tin-based perovskite is ASnX3,

[0010] Wherein: A is selected from cesium (Cs + ), rubidium (Rb + ), methylamine (MA + ), formamidine (FA + ), X is selected from at least one of Cl, Br, and I.

[0011] In the present application, the tin halide may be selected from one or more of tin iodide, tin bromide, and tin chloride. The total concentration of the tin halide may be 0.0001-10 mol / L, preferably 0.2 mol / L.

[0012] Furthermore, the acidic substrate has an acidic group, and the acidic group includes at least one of a sulfonic acid group, a phosphoric acid group, and a carboxylic acid group, for example: PEDOT:PSS, P3CT.

[0013] Further, the monovalent cation halide includes at least one of cesium halide, rubidium halide, methylamine halide, and formamidine halide;

[0014] The halide includes at least one of chloride, bromide and iodide.

[0015] Furthermore, the perovskite precursor solution also includes a sacrificial agent to compensate for the oxidized Sn 2+ The molar ratio of stannous fluoride to tin halide is (0.01-1):1.

[0016] Preferably, the molar ratio between the stannous fluoride and the tin halide is 0.1:1.

[0017] In this application, tin halides are mainly used to form perovskite structures. SnF2 cannot form perovskite due to the small radius of the F ion. The main function of stannous fluoride is to act as a sacrificial agent to compensate for the oxidized Sn. 2+ , while improving the crystal morphology.

[0018] Furthermore, the ethylenediamine derivative is a derivative containing an ethylenediamine structure and having different substituent groups;

[0019] The derivatives include at least one of N-benzylethylenediamine (BEA), N-methylethylenediamine, N-ethylethylenediamine (EEA), N-propylethylenediamine, N-isopropylethylenediamine, N-hexylethylenediamine, and N-adamantylethylenediamine. The inventors have found that different substituents can adjust the coordination ability of ethylenediamine derivatives.

[0020] Furthermore, the thiocyanate includes one or more of ammonium thiocyanate (NH4SCN), sodium thiocyanate (NaSCN), stannous thiocyanate (Sn(SCN)2), and methylamine thiocyanate (MASCN).

[0021] Furthermore, the solvent used in the perovskite precursor solution is dimethyl sulfoxide (DMSO), N',N-dimethylformamide (DMF) and a mixture of the two in any proportion.

[0022] Further, the molar ratio of the tin halide, the monovalent cation halide, the thiocyanate, and the ethylenediamine derivative is:

[0023] 1:(0.1-3):(0.0001-1):(0.0001-2).

[0024] Preferably, the molar ratio of the tin halide, the monovalent cation halide, the thiocyanate, and the ethylenediamine derivative is 1:1:0.4:0.08.

[0025] Furthermore, the annealing parameters in step S2 are:

[0026] The annealing temperature is 20-200°C and the annealing time is at least 10s;

[0027] And the transformation of the induced complex intermediate phase to the tin-based perovskite film is completed within the annealing time of 0-60s.

[0028] Preferably, the annealing condition is 140° C. for 5-6 minutes.

[0029] A light-emitting diode device comprises a substrate, a transparent electrode, a hole transport layer, a light-emitting layer, an electron transport layer, an electron injection layer, and a metal electrode, which are stacked in sequence. The light-emitting layer is a tin-based perovskite film prepared by the above method.

[0030] Beneficial effects of the present invention:

[0031] (1) The present invention introduces ethylenediamine derivatives into the tin-based perovskite precursor solution to coordinate with the tin-based precursor, thereby changing the perovskite crystallization process, and first forming a complex intermediate phase after spin coating. Then, annealing treatment is performed to promote the conversion of the complex intermediate phase into a perovskite film by using the protonation reaction between the acidic substrate and the ethylenediamine derivative, effectively improving the film coverage and reducing the roughness. At the same time, by adding thiocyanate to inhibit Sn 2+ Oxidation effectively improves the performance of PeLED devices.

[0032] (2) The present invention provides a new idea for the crystallization regulation of perovskite, and gives different meanings to spin coating and annealing. At the same time, the crystallization of perovskite in the spin coating process in the prior art is transferred to the crystallization of perovskite in the annealing process. The interface reaction-assisted crystallization strategy effectively inhibits the rapid crystallization of tin-based perovskite, improves the film morphology and reduces the defect density, and promotes the further improvement of the stability of tin-based perovskite optoelectronic devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 Schematic diagram of the preparation process of the perovskite film in Example 1;

[0034] Figure 2 Schematic diagram of the protonation reaction in Example 1: Under the action of organic amine, the perovskite precursor solution first forms a complex intermediate phase during the spin coating process, and during the annealing process, the organic amine reacts with the acidic PEDOT:PSS substrate to undergo a protonation reaction, inducing the complex intermediate phase to transform into a tin-based perovskite;

[0035] Figure 3 The data are the characterization data of the complex formed by N-benzylethylenediamine (BEA) and SnBr2 in the perovskite precursor in Example 1; a is an optical photograph after BEA is added to the SnBr2 solution; b is the NMR spectrum of the mixed solution of BEA and SnBr2 (the solvent is deuterated DMSO); c is the infrared spectrum of the mixed solution;

[0036] Figure 4 The crystallization process of the perovskite film of Example 1 and Comparative Example 1 is monitored; a is an optical photograph of CsSnBr3 (reference film, Comparative Example 1) and a film with added BEA (CsSnBr3-BEA) after spin coating; b is an X-ray diffraction spectrum of the reference film and the film after spin coating with CsSnBr3-BEA; c is a graph showing the relationship between the perovskite absorption signal of the reference film and the film after spin coating with CsSnBr3-BEA during the annealing process and the time;

[0037] Figure 5 N1s XPS spectra of CsSnBr3-BEA films prepared on different substrates;

[0038] Figure 6is a reference film prepared on PEDOT:PSS ( Figure 6 a) Scanning electron microscope (SEM) images of CsSnBr3-BEA thin films ( Figure 6 b);

[0039] Figure 7 is a reference film prepared on PEDOT:PSS ( Figure 7 a) Atomic force microscope (AFM) images of CsSnBr3-BEA thin films ( Figure 7 b);

[0040] Figure 8 The fluorescence (PL) spectra of the reference film and CsSnBr3-BEA film prepared on PEDOT:PSS;

[0041] Fig. 9 X-ray diffraction (XRD) spectra of the reference film and the perovskite film of Example 2 (denoted as BEA-KSCN film);

[0042] Fig.10 Sn 3d XPS spectra; a is the reference film, b is the BEA-KSCN film;

[0043] Fig.11 is the fluorescence spectra of the reference film and BEA-KSCN film;

[0044] Fig.12 The performance of the perovskite LED device based on the reference film of Comparative Example 2 and the BEA-KSCN film of Example 2; a is the structure of the perovskite LED device; b is the current density-voltage-brightness curve; c is the EL spectrum; d is the EQE-current curve of the optimal device;

[0045] Fig.13 is the performance of the perovskite LED device of Example 3; a is the current density-voltage-brightness curve; b is the EQE-current curve of the optimal device;

[0046] Fig.14 is the performance of the perovskite LED device of Example 4; a is the current density-voltage-brightness curve; b is the EQE-current curve of the optimal device;

[0047] Fig.15 is the performance of the perovskite LED device of Example 5; a is the current density-voltage-brightness curve; b is the EQE-current curve of the optimal device;

[0048] Fig.16 is the performance of the perovskite LED device of Example 6; a is the current density-voltage-brightness curve; b is the EQE-current curve of the optimal device;

[0049] Fig.17 : is the performance of the perovskite LED device of Example 7; a is the current density-voltage-brightness curve; b is the EQE-current curve of the optimal device. DETAILED DESCRIPTION

[0050] In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific implementation methods described here are only used to explain the present invention and are not used to limit the present invention.

[0051] Embodiment 1:

[0052] A method for in-situ film formation of perovskite assisted by interface protonation reaction comprises the following steps:

[0053] Dissolve CsBr, SnBr2, SnF2 and KSCN in DMSO solution at a molar ratio of 1:1:0.1:0.4 to prepare a precursor solution with a SnBr2 concentration of 0.2 mol / L and add 5 mg / mL tin powder. Continue heating and stirring at 600 rpm on a heating table at 60°C for more than 2 hours to fully dissolve the drugs. After dissolution, filter through a 0.22 um hydrophilic filter head, add 2 mg of benzylethylenediamine, mix well, and let stand for 24 hours to obtain a perovskite precursor solution.

[0054] After filtering the PEDOT:PSS solution through a 0.22um hydrophilic filter, take 30ul and drop it on a quartz or ITO substrate, spin-coat it at 5000rpm for 60s, and then anneal it in an air environment at 150℃ for 30min to obtain a PEDOT:PSS substrate.

[0055] The PEDOT:PSS substrate was transferred to a nitrogen atmosphere glove box and placed in the center of the chuck of the spin coater. 40 μL of the perovskite precursor solution in Example 1 was pipetted and dripped onto the substrate. The spin coating parameters were set to a speed of 4000 r / min and a duration of 60 s. The substrate was then annealed on a hot plate at 140°C for 5 min.

[0056] like Figure 3 As shown in a, obvious changes in color and absorption spectrum can be observed when BEA is added to the perovskite precursor solution. Figure 3 b and Figure 3 c shows the H NMR spectra of pure BEA (solute is BEA, solvent is DMSO) and BEA-SnBr2 mixed solution, respectively. It can be seen that the chemical environment of the methylene and amine groups of the BEA molecule in BEA-SnBr2 has changed. Figure 3 c The shift of NH vibration peak in the infrared spectrum shows that there is a coordination effect between BEA molecules and SnBr2 in the precursor solution.

[0057] like Figure 4 As shown in a, this coordination effect allows the perovskite precursor solution to form an intermediate phase first after spin coating. Figure 4 b XRD analysis shows that the intermediate phase is an amorphous phase. Figure 4 c is the change in the absorption spectrum of the perovskite film during the annealing process. It can be seen that the intermediate phase transforms into perovskite during the annealing process.

[0058] like Figure 5 As shown in the figure, the protonated amine groups (-NH3 + ) signal, indicating that the intermediate phase transition process is accompanied by the protonation reaction of PEDOT:PSS substrate and BEA.

[0059] like Figure 6 b and Figure 7 As shown in b, the perovskite film formed by the interface reaction assisted crystallization strategy has higher film coverage and lower roughness.

[0060] like Figure 8 As shown, the perovskite film formed by the interface reaction-assisted crystallization strategy has a higher fluorescence intensity.

[0061] Embodiment 2:

[0062] High-performance tin-based PeLED devices were prepared using an interfacial reaction-assisted crystallization method and a thiocyanate antioxidant strategy.

[0063] Dissolve CsBr, SnBr2, SnF2 and KSCN in DMSO solution at a molar ratio of 1:1:0.1:0.4, prepare a SnBr2 solution with a concentration of 0.2 mol / L and add 5 mg / mL tin powder. Continue heating and stirring at 600 rpm on a heating table at 60°C for more than 2 hours to fully dissolve the drugs. After dissolution, filter through a 0.22 um hydrophilic filter head, add 2 mg N-benzylethylenediamine, mix well, and let stand for 24 hours for use.

[0064] A tin-based PeLED device was prepared, and the device structure was indium tin oxide (ITO, anode)-PEDOT:PSS (hole transport layer)-perovskite light-emitting layer-TPBi (electron transport layer)-LiF / Al electrode (cathode), wherein the preparation / treatment methods of each functional layer were as follows:

[0065] (1) Cleaning of indium tin oxide (ITO) glass sheet: Wipe a glass sheet (19.8×19.8 mm) sputtered with 135 nm thick ITO with a dust-free cloth dipped in ethanol, place it in a polytetrafluoroethylene cleaning rack, place the beaker with the cleaning rack in an ultrasonic cleaner, add deionized water, ethanol, acetone, and ethanol to cover the ITO glass sheet in sequence, and ultrasonicate for 10 min each time; take out the cleaned ITO glass sheet, and use a nitrogen gun to blow dry the ethanol attached to the surface of the ITO glass sheet; place the blown-dried ITO glass sheet in a glass culture dish with the ITO surface facing up, and further clean it with an oxygen plasma cleaner, and wash it for 10 min after it glows.

[0066] (3) Preparation of PEDOT:PSS hole transport layer: see Example 1 for details

[0067] (4) Preparation of perovskite light-emitting layer: see Example 1 for details

[0068] (5) The preparation of the TPBi electron transport layer and the preparation of the LiF electrode are both prior arts and will not be described in detail here. Please refer to the Chinese patent publication number CN118302018A.

[0069] like Fig. 9 As shown, the BEA-KSCN film has a crystal structure consistent with that of CsSnBr3, indicating that the addition of KSCN does not affect the perovskite structure.

[0070] like Fig.10 As shown in Figure 2, the tetravalent tin content in the BEA-KSCN film decreased significantly, indicating that KSCN can effectively inhibit Sn 2+ Oxidation.

[0071] like Fig.11 As shown, the fluorescence intensity of BEA-KSCN film is significantly improved.

[0072] like Fig.12 As shown in b, the PeLED device based on BEA-KSCN film has a luminescent wavelength of 676 nm. Fig.12 As shown in c, the device based on BEA-KSCN film has lower dark current and significantly improved brightness compared to the device based on the reference film.

[0073] like Fig.12 As shown in (d), the EQE of the PeLED device based on BEA-KSCN film is greatly improved.

[0074] Embodiment 3-7:

[0075] The difference from Example 2 is that the ethylenediamine derivatives of Examples 3-7 are replaced with N-methylethylenediamine, N-ethylethylenediamine, N-propylethylenediamine, N-hexylethylenediamine, and N-adamantylethylenediamine in sequence.

[0076] like Figure 13-17 As shown, different ethylenediamine derivatives can effectively improve the device brightness and EQE.

[0077] Comparative Example 1:

[0078] Compared with Example 1, N-benzylethylenediamine was not added to the precursor solution (i.e., the reference film). The above examples and comparative examples were tested and analyzed, and the analysis results are as follows:

[0079] like Figure 4 As shown in a, the reference film has changed color after spin coating and emits red fluorescence under 365nm excitation. Figure 4 b XRD analysis shows that the reference film has CsSnBr3 diffraction peak signal after spin coating. Figure 4 c is the change in the absorption spectrum of the perovskite film during the annealing process. It can be seen that only a small amount of perovskite growth occurs in the reference film during the annealing process. It can be seen that the reference film has a faster crystallization speed and has been crystallized during the spin coating process. During the annealing process, only the perovskite growth process caused by the evaporation of residual solvent occurs.

[0080] like Figure 6 a and Figure 7 As shown in a, the reference film has a lower coverage than the CsSnBr3-BEA film and the film is rougher.

[0081] like Figure 8 As shown, the reference film has low fluorescence intensity and high defect density.

[0082] It can be seen that the interface reaction-assisted crystallization strategy effectively inhibits the rapid crystallization of tin-based perovskite, improves the film morphology and reduces the defect density.

[0083] Comparative Example 2:

[0084] Compared with Example 2, BEA and KSCN are not added to the precursor solution (ie, PeLED device based on reference film). The above examples and comparative examples are tested and analyzed, and the analysis results are as follows:

[0085] like Fig.12 As shown in c, the PeLED device in Comparative Example 2 has a higher dark current and a lower brightness.

[0086] like Fig.12 As shown in d, the perovskite LED device in Comparative Example 2 has a lower EQE.

[0087] Therefore, it can be seen that the interface reaction-assisted crystallization strategy and the thiocyanate antioxidant strategy of the present application can effectively improve the performance of tin-based perovskite LED devices.

[0088] The present invention illustrates the detailed preparation method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed preparation method, that is, it does not mean that the present invention must rely on the above-mentioned products and detailed preparation methods to be implemented. It should be clear to those skilled in the art that any improvement of the present invention, the combination or equivalent replacement of the raw materials of the product of the present invention, all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for in-situ film formation of perovskite assisted by interfacial protonation reaction, characterized in that: The steps include: S1, spin coating: spin coating a perovskite precursor solution on an acidic substrate to form a complex intermediate phase; the perovskite precursor solution includes a tin halide, a monovalent cation halide, a thiocyanate, and an ethylenediamine derivative; S2, annealing: heating and annealing the complex intermediate phase on a hot stage, inducing the transformation of the complex intermediate phase into a tin-based perovskite film through a protonation reaction between the acidic substrate and the ethylenediamine derivative; the chemical structure of the tin-based perovskite is ASnX3, Wherein: A is selected from cesium (Cs + ), rubidium (Rb + ), methylamine (MA + ), formamidine (FA + ), X is selected from at least one of Cl, Br, and I.

2. The method of in-situ film formation of perovskite assisted by interfacial protonation reaction according to claim 1, characterized in that: The acidic substrate has an acidic group, and the acidic group includes at least one of a sulfonic acid group, a phosphoric acid group, and a carboxylic acid group.

3. The method for in-situ film formation of perovskite assisted by interfacial protonation reaction according to claim 1, characterized in that: The monovalent cation halide includes at least one of cesium halide, rubidium halide, methylamine halide, and formamidine halide; The halide includes at least one of chloride, bromide and iodide.

4. The method of in-situ film formation of perovskite assisted by interfacial protonation reaction according to claim 1, characterized in that: The perovskite precursor solution also includes a sacrificial agent to compensate for the oxidized Sn 2+ The molar ratio of stannous fluoride to tin halide is (0.01-1):

1.

5. The method for in-situ film formation of perovskite assisted by interfacial protonation reaction according to claim 1, characterized in that: The ethylenediamine derivatives are derivatives containing ethylenediamine structures and having different substituent groups; The derivative includes at least one of N-benzylethylenediamine (BEA), N-methylethylenediamine, N-ethylethylenediamine (EEA), N-propylethylenediamine, N-isopropylethylenediamine, N-hexylethylenediamine, and N-adamantylethylenediamine.

6. The method of in-situ film formation of perovskite assisted by interfacial protonation reaction according to claim 1, characterized in that: The thiocyanate includes one or more of ammonium thiocyanate (NH4SCN), sodium thiocyanate (NaSCN), stannous thiocyanate (Sn(SCN)2), and methylamine thiocyanate (MASCN).

7. The method of in-situ film formation of perovskite assisted by interfacial protonation reaction according to claim 1, characterized in that: The solvent used in the perovskite precursor solution is dimethyl sulfoxide (DMSO), N',N-dimethylformamide (DMF) and a mixture of the two in any proportion.

8. The method of in-situ film formation of perovskite assisted by interfacial protonation reaction according to claim 1, characterized in that: The molar ratio between the tin halide, the monovalent cation halide, the thiocyanate, and the ethylenediamine derivative is: 1:(0.1-3):(0.0001-1):(0.0001-2)。 9. The method of in-situ film formation of perovskite assisted by interfacial protonation reaction according to claim 1, characterized in that: The annealing parameters in step S2 are: The annealing temperature is 20-200°C and the annealing time is at least 10s; And the transformation of the induced complex intermediate phase to the tin-based perovskite film is completed within the annealing time of 0-60s.

10. A light emitting diode device, characterized in that: It comprises a light-emitting layer prepared by the method according to any one of claims 1 to 9, wherein the light-emitting layer is a tin-based perovskite film.

Citation Information

Patent Citations

  • Perovskite light emitting diode containing interface modification layer and preparation method thereof

    CN118302018A

Cited By

  • Preparation method of tin-based perovskite thin film

    CN122054896A

  • A method for preparing a tin-based perovskite thin film

    CN122054896B